Remdesivir use in pregnant women with severe COVID-19 - Mamilla, Sarada; Boorugu, Harikishan; B. P. L., Ramya Bharghavi; Kodam, Bhavana Priya; Adapa, Sandhya Rani; Kamani, Gayathri; Vuta, Tejaswi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Numerous therapeutic strategies are proposed and tested for SARS CO-V2 infection. Remdesivir is researched and proposed by various societies. Studies about efficacy and safety in pregnancy are limited. A case series of 22 pregnant women effected with severe COVID disease and who received remdesivir, over a period of 1 year from May 2020 to May 2021 is presented. The 12 antenatal and 10 post-partum women were included. Demographic factors, baseline, day 3 and day 7 blood values of haemoglobin, total leukocyte count, platelets, liver enzymes, serum creatinine and D-dimers were collected. Adverse events were reported. Pregnancy complications and foetal and neonatal complications were studied. Pre-eclampsia was the most common comorbidity. The 99% of pregnant women and 100% of postpartum women recovered from COVID disease after remdesivir use. Lab investigations did not change considerably during the week of remdesivir use, suggesting its safety. Incidence of adverse events reported is 36.3%, of these 9% are serious adverse events. There are no antenatal or post-natal complications. No incidence of teratogenicity, foetal or neonatal complications. Incidence of feto-maternal transmission was 9%. Remdesivir is effective in treating severe SARS-CoV2 infection and has safety profile in pregnancy with regard to maternal and foetal effects.